2015
DOI: 10.1016/j.cpet.2014.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Utility of PET in Prostate Cancer

Abstract: Accurate prediction and assessment of relevant outcomes is important in clinical trial design and in clinical practice for selecting and sequencing appropriate individualized management of patients with prostate cancer. There have been many standard non-imaging based prediction tools for the various phases of prostate cancer. However these tools may be limited in individual cases and need updating based on the improved understanding of the underlying complex biology of the disease and the emergence of the nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Relevant outcome measures in prostate cancer may include, but are not limited to, time to biochemical recurrence (time to PSA progression), time to first metastasis, time to symptomatic progression, time to initiation of cytotoxic chemotherapy, time to radiographic progression, time to castrate resistance state, progression-free survival (PFS), metastasis-free survival, disease-specific survival, and overall survival (33). One study of 42 men with primary prostate cancer showed that patients with higher primary tumor FDG uptake had significantly poorer prognosis compared to those patients with tumors that showed lower FDG uptake (34).…”
Section: Prognosis Assessmentmentioning
confidence: 99%
“…Relevant outcome measures in prostate cancer may include, but are not limited to, time to biochemical recurrence (time to PSA progression), time to first metastasis, time to symptomatic progression, time to initiation of cytotoxic chemotherapy, time to radiographic progression, time to castrate resistance state, progression-free survival (PFS), metastasis-free survival, disease-specific survival, and overall survival (33). One study of 42 men with primary prostate cancer showed that patients with higher primary tumor FDG uptake had significantly poorer prognosis compared to those patients with tumors that showed lower FDG uptake (34).…”
Section: Prognosis Assessmentmentioning
confidence: 99%
“…In the clinical setting of prostate cancer, these outcome measures may include, but are not limited to, time to biochemical recurrence (time to PSA progression), time to first metastasis, time to symptomatic progression, time to initiation of cytotoxic chemotherapy, time to radiographic progression, time to castration resistance state, progression-free survival, metastasis-free survival, disease-specific survival, and overall survival (29).…”
Section: Assessment Of Prognosismentioning
confidence: 99%
“…In recent years, molecular imaging with positron emission tomography coupled with computed tomography (PET/ CT) has been developed to stage cancers [14]. One of the most commonly used PET tracers is 18 F-fluorodeoxyglucose (FDG), which is preferentially taken up by malignant cells due to increased glucose metabolism known as the "Warburg effect" [15].…”
mentioning
confidence: 99%